Dynamic description technology of fractured vuggy carbonate gas reservoirs - Jiang, Tongwen; Sun, Hedong; Deng, Xingliang (Gulf Professional Publishing, 2019)
Dynamic Description Technology of Fractured Vuggy Carbonate Gas Reservoirs delivers a critical reference to reservoir and production engineers on the basic characteristics of fractured vuggy gas reservoirs, combining both static and dynamic data to improve reservoir characterization accuracy and development. Based on the full lifecycle of well testing and advanced production decline analysis, this reference also details how to apply reservoir dynamic evaluation and reserve estimation and performance forecasting. Offering one collective location for the latest research on fractured gas reservoirs, this reference also covers physical models, analysis examples, and processes, 3D numerical well test technology, and deconvolution technology of production decline analysis. Packed with many calculation examples and more than 100 case studies, this book gives engineers a strong tool to further exploit these complex assets.
Includes index.
Keywords: Petroleum engineering.; elektronické knihy; electronic books